2010
DOI: 10.3928/01913913-20100118-03
|View full text |Cite
|
Sign up to set email alerts
|

Convergence Excess Esotropia: A Proposed New Classification and the Effect of Monocular Occlusion on the Ac/A Ratio

Abstract: Ac/A ratio measurement in convergence excess esotropia is influenced by fusional tenacity. Disrupting this fusion with a period of monocular occlusion results in changes to the angle of deviation in some patients, suggesting subcategorization of this condition into true and simulated convergence excess esotropia. Measurements of the Ac/A ratio are influenced by fixation distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It is postulated that tenacious fusion masks the true distance angle of deviation in many patients with convergence excess in a similar way as described by Kushner 7 and Rosenfield et al 8 in intermittent exotropia. The author's previous paper investigating convergence excess esotropia 17 suggested two subcategories of convergence excess accommodative esotropia:…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that tenacious fusion masks the true distance angle of deviation in many patients with convergence excess in a similar way as described by Kushner 7 and Rosenfield et al 8 in intermittent exotropia. The author's previous paper investigating convergence excess esotropia 17 suggested two subcategories of convergence excess accommodative esotropia:…”
Section: Discussionmentioning
confidence: 99%
“…5 Garretty 16 reported an annual incidence in Leeds of six new cases per year (city population ¼ 443 000). Kutschke and Keech 17 measured the gradient AC/A ratio in 62% of their DND cases.…”
Section: Hypermetropic Undercorrectionmentioning
confidence: 99%
“…Kushner 11 further reported that a longer period of sustained occlusion prior to measurement significantly altered the ratio, which therefore changed the classification of the patient's condition. The use of monocular occlusion in this way has also been investigated in relation to CXS by Garretty,14 who found monocular occlusion prior to measurement of the AC/A ratio resulted in two clinically and statistically distinct groups. The conclusion was that CXS could be sub-categorised in a similar way to IDEX.…”
Section: Specifics Of Testing Techniquesmentioning
confidence: 99%